Providing Neurodynamic Mobilization Exercises is Better than Myofascial Release in Improving Complaints in Construction Workers with Carpal Tunnel Syndrome in Cahaya Dinar Housing - Sadu, Bernad; Wicaksono, Utomo; Proyogo, Dadan (Sean Institute, 2022)
Background : Carpal tunnel syndrome (CTS) is a collection of symptoms that appear along the median nerve innervation area, caused by compression or pressure on the (median) nerve in the wrist area or carpal tunnel. Neurodynamic mobilization exercises are tension (stretching) and sliding (sliding) techniques to move the nerve structures proximal and distal parts of the nerve, involving the spine (neck) and hands). Myofascial release is a therapeutic method using the hands to release adhesions or bonds in myofascial tissue. This research aims to prove application of mobilization neurodynamics in repair complaints Method: This study Uses an experimental pretest-posttest control group design. Amount subject study 16 people divided into two groups, group treatment 1 was given intervention practice mobilization neurodynamics, and group treatment 2 was given myofascial release. Intervention gave 3 per week for 4 weeks. The instrument study uses Boston Carpal Tunnel Questionnaire (BCTQ). Result: Measurement result complaint pretest and posttest on groups treatment 1 and treatment 2 equally showing repair with p-value 0.000. Comparison test results effectiveness showing a meaningful difference where practice mobilization neurodynamics better in repair CTS complaints with p-value 0.000. Conclusion: Mobilization exercise neurodynamics and myofascial release both can provide repair, however, practice mobilization neurodynamics has proven better inside repair complaints against workers buildings experiencing CTS.